Pharmacovigilance in the handling of anticancer agents biosafety practices of healthcare workers in four tertiary hospitals in Metro Manila - Velasco, Jackie Lyn T. David
Background: Globally there is now an advocacy on pharmacovigilance and biosafety in handling of anticancer agents because handling of these agents poses a significant health risk to health care workers handling them. In this research endeavor, the investigator aim to determine if international guidelines on safe handling of anticancer agents are adapted in local oncology settings. Objectives:1) to determine if representative tertiary hospitals with oncology units have policies (SOPs) pertaining to safe handling of anticancer agents and if they have the environment and equipment required in compounding of anticancer agents; 2) to determine the biosafety practices of healthcare workers in handling of anticancer agents in terms of use of PPE, cleaning and decontamination, cytotoxic spill and waste management 3) to determine the risks the health care workers have in their current practices. Methodology: Cross sectional analytic design using survey questionnaires, observation checklists, focused group discussions and video documentation of compliance with guidelines and actual biosafety practices. Participants: Consultants, fellows, nurses, nursing attendants and pharmacists who presently handle chemotherapy drugs in any of the following activities: preparation and compounding, administration, removal of IV lines and disposal of cytotoxic waste, in: Philippine General Hospital, Jose Reyes Memorial Medical Center, The Medical City and Cardinal Santos Medical Center. Analysis: Descriptive Statistics including measures of central tendency for numerical data and frequency distribution for categorical data. Results: There were a total of 96 respondents, with 22 males (23%) with the mean age in years of 31(+ 7.64). Majority of the respondents are nurses (56%) followed by physicians, pharmacists and nursing attendants. The private hospitals have SOP's pertaining to safe handling of anticancer agents that are implemented while the government hospitals do not have any. Use of standard equipment such as an isolator and a biological safety cabinet (BSC) were observed in the private hospitals. Health care workers do not have consistently use Personal Protective Equipment (PPE) and PPE employed are not the standard type. Regular cleaning and decontamination is oncology units in the private hospitals but not in the government hospitals. Majority of the health care workers claim they know how to manage a cytototic spill, however, spill kits which are required in the management of spills are only available in the private hospitals. Majority of health care workers segregate cytotoxic waste from other hospital wastes, but where these wastes are disposed of by their hospitals is unknown by them. There is no special medical surveillance program to monitor health status of personnel who regularly handle anticancer agents in any of he hospitals. Majority also feel they need further training in safe handling. Drug compounding, administration and removal of IV lines and IV solutions were the most frequently performed activities and where cytotoxic spills, contamination and accidental contact usually happens. The most frequently handled anticancer drugs are known to be strong vessicants and irritants and can tissue irritation and tissue necrosis during accidental contact. Self experience of adverse where claimed by some participants. Half of the study population had a family history of cancer. Conclusion: The practice of biosafety in the Philippines is inconsistent, sporadic and not complaint with the guidelines in safe handling of anticancer agents, leaving many health care workers potentially exposed and at risk of experiencing acute and long term adverse effects. Recommendations: It is recommended to further study strict compliance to aseptic techniques and biosafety practices and to conduct similar studies in other areas where chemotherapy services is provided. It is also recommended that professional organizations governing such practice must initiate an awareness campaign on biosafety practices to protect the health and welfare of the professionals who engage in oncology practice.